Interactions and relationships in adults with intellectual disability - Clegg, Jennifer (1990)
This research concerned the social experience of two groups of adults with intellectual disability (mental handicap), those with verbal skills who could describe their experience and those with profound disabilities whose needs were interpreted by carers. Conceptual issues have been discussed to provide a framework for understanding their relationships and also for understanding intellectual disability itself. Social constructionism, has influenced the investigations.